The Impact of Halal Knowledge and Attitudes on Purchase Intention: Insights From Sabah, Malaysia - Nurul Atiqa Mohd Tahir; Aizul Azri Azizan; Sharifudin Md Shaarani; Noor Qhairul Izzreen Md Nor; Umi Hartina Mohamad Razali; Ahmad Riduan Bahauddin (Faculty of Food Science and Nutrition, Universiti Malaysia Sabah, 2026)
Non-Indexed Publication